The Influence of Literacy Culture, Family Roles, and Learning Discipline on Student Learning Achievement At MA Tanada Waru Sidoarjo - Azizah, Cholifatul; Darmawan, Didit (IAIN KENDARI, 2025)
Learning achievement is the level of student results that can be seen and proven during the learning process, unfortunately this is not evenly distributed, because the abilities and characteristics of each student are not the same. The researcher compiled this study with the aim of proving that there is an influence of literacy culture, family roles, and learning discipline on student learning achievement. The research was conducted using a quantitative survey method through observation, questionnaires, and documentation. The number of sample populations selected by the researcher was all 36 students, using a sample technique, namely total sampling because the number was less than 100. The researcher distributed questionnaire statements by providing a google form. Data analysis with data quality tests, classical assumption tests, and regression tests with the help of IBM SPSS version 26. Based on the results during the study, it was proven that from the literacy culture variable there was no correlation, meaning there was no significant influence because one of the causes was the lack of book facilities in schools. Other than the results of the family role and learning discipline variables, they were different, namely showing a significant effect, these results indicate that support from the family and students' disciplinary attitudes in learning are needed to achieve learning achievement. This finding concludes that literacy culture does not affect student learning achievement, while the role of family and learning discipline affect student learning achievement of MA TANADA Waru Sidoarjo students. This is very necessary to improve student learning achievement with aspects that can influence it.